Chaos and Convergence on Bucket Brigade Assembly Lines - Bartholdi, III, John J. (Institutional Knowledge at Singapore Management University, 2007)
One way to coordinate the efforts of workers along an assembly line that has fewer workers than work stations is to form a bucket brigade. Each worker in a bucket brigade simultaneously assembles a single item (an instance of the product) along the line. The worker carries the item from work station to work station until either he hands of his item to a downstream co-worker or he completes the work for his item. The worker then walks back to get another item, either from his co-worker upstream or from a buffer at the beginning of the line. The most notable application of bucket brigades is to coordinate workers to pick products for customer orders in distribution centers, as reported in Bartholdi and Eisenstein (1996b) and Bartholdi et al. (2001). Bucket brigades have also been used in the production of garments, the packaging of cellular phones, and the assembly of tractors, large-screen televisions, and automotive electrical harnesses (see Bartholdi and Eisenstein (1996a,b, 2005), and Villalobos et al. (1999a,b)).